Home / Mathematics / Trigonometry / Prove that: 1/secA-tanA – 1/cosA = 1/cosA – 1/secA-tanA

Prove that: 1/secA-tanA – 1/cosA = 1/cosA – 1/secA-tanA

Solution:

or, 1/(secA-tanA) + 1/ (secA+tanA) = 1/cosA + 1/cosA

or, (secA+tanA + secA-tanA)/(secA-tanA )(secA+tanA)= secA + secA

Or, 2secA/(sec2A-tan2A)=2secA

Therefore, 2secA=2secA

proved

About Arjun Dhamala

Arjun Dhamala is the CEO of thereadmore.com. He is the student of statistics and permanent resident of Nepal. He is one of the Author in this website. Writing, reading and travelling are his hobbies.

Leave a Reply

Your email address will not be published. Required fields are marked *